Analisis Pengaruh Kecepatan Putaran Rol Terhadap Efisiensi Pengupasan Pada Mesin Pengupas Sabut Kelapa - Tri agung; Riandadari, Dyah; Sakti, Arya Mahendra; Nugroho, Aji (Universitas Negeri Surabaya, 2026)
Abstract: This study aims to analyze the effect of roller rotational speed variations on the efficiency, capacity, and quality of coconut husk peeling in a coconut husk peeling machine using small- and large-sized coconuts as test objects. The roller rotational speed variations applied were 120 rpm, 150 rpm, 180 rpm, 210 rpm, and 240 rpm, where the rotational speed served as the main parameter influencing peeling time, process success rate, and the potential for coconut damage. The research employed an experimental method through direct performance testing of the machine, with observation parameters including peeling time, machine capacity (fruits/hour), and peeling efficiency (%). The test results showed that at rotational speeds of 120 rpm and 150 rpm, the peeling efficiency of small coconuts reached 100%, while the peeling efficiency of large coconuts remained relatively low at 70% and 60%, respectively. At a rotational speed of 180 rpm, the peeling efficiency of large coconuts increased to 100%, with a machine capacity of 563 fruits/hour. Increasing the roller rotational speed to 210 rpm and 240 rpm further enhanced the machine capacity to 784 fruits/hour and 849 fruits/hour, respectively, while reducing the average peeling time to 4.2 seconds. However, at these higher speeds, the peeling efficiency of small coconuts decreased due to the increased mechanical forces acting on the material. Based on the results, a roller rotational speed of 180 rpm was identified as the most optimal condition, as it provided high peeling efficiency, adequate machine capacity, and good peeling quality without causing significant damage to the coconuts.